Professional Education for Social Work in Britain: An Historical Account (A Book Review) - Rugaya Tuanaya; Nurdin Buatan (ASSUNNAH PRESS, 2024)
This article is a review of Marjorie J. Smith's book, Professional Education for Social Work in Britain: An Historical Account, 2022. We present a comprehensive historical expression of the evolution of vocational education for social workers in the United Kingdom in the late 19th and early 20th centuries. The focus was on the initial training methods in social workers institutions, the transition to formal training schemes, the establishment and challenges of the School of Sociology, as well as the merger with the London School of Economics (LSE). This paper explores the ongoing tension between academic education and practical professional training in social work. As a valuable resource, this paper outlines the philosophical foundations, pedagogical approaches, and institutional challenges that shape social worker training. Through historical exhibitions, committee reports, and practical work reports, this paper provides a rich narrative that emphasises the importance of comprehensive education that integrates theoretical knowledge with practical skills. The review assesses the content, structure, and contribution of this book to the field of social worker education, exploring the target audience, advantages, and potential constraints as well as their relevance in contemporary discussions on training and preparation of social workers. In conclusion, the merger of the School of Sociology with the London School of Economics is not only a strategic step to maintain the quality and coverage of social worker education but also depicts further reflection on narratives that integrate social thinking and action into a more sustainable institutional framework.